2022
DOI: 10.1038/s41598-022-26907-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of age-specific causes of death in the context of the Italian longevity transition

Abstract: In many low-mortality countries, life expectancy at birth increased steadily over the last century. In particular, both Italian females and males benefited from faster improvements in mortality compared to other high-income countries, especially from the 1960s, leading to an exceptional increase in life expectancy. However, Italy has not become the leader in longevity. Here, we investigate life expectancy trends in Italy during the period 1960–2015 for both sexes. Additionally, we contribute to the existing li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Therefore, it is important to investigate the age-specific differences between the real and the estimated mortality data according to specific phases of longevity evolution namely regularities, improvements, and stagnation, that can be represented by Japan, Italy, and the USA respectively. Specifically, Italian life expectancy exhibits a long-run transition with considerably upward shifts, converging to longevity records (Nigri et al 2021a, 2022b, 2022c). This result has been achieved by a mix of a relatively healthy lifestyle and an efficient health system.…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to investigate the age-specific differences between the real and the estimated mortality data according to specific phases of longevity evolution namely regularities, improvements, and stagnation, that can be represented by Japan, Italy, and the USA respectively. Specifically, Italian life expectancy exhibits a long-run transition with considerably upward shifts, converging to longevity records (Nigri et al 2021a, 2022b, 2022c). This result has been achieved by a mix of a relatively healthy lifestyle and an efficient health system.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…The literature devoted to the longevity model for indirect estimation is based on the deep learning model. Indeed, more recently, Nigri et al (2022d) formalized a deep neural networks approach to indirectly derive age-specific mortality from observed or predicted life expectancy by leveraging deep learning algorithms akin to demography’s indirect estimation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several studies reporting the evolution of mortality and life expectancy in Italy (among the most recent, Nigri et al, 2022), there are only a few studies that explore trends in DFLE for the country. Frova et al (2010) found that, between 1994 and 2005, both life expectancy and DFLE increased, and that gender differences in DFLE gradually reduced.…”
Section: Introductionmentioning
confidence: 99%